Exploring the role of personality traits as mediators of mental health in Pakistani commuters - Alia Asmat; Niazi, Nazish; Choudary, Ginasha (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate how resilience mediates the relationship of personality factors with depression and aggression among daily commuters in an urban setting. Method: The correlational study was conducted at Lahore Pakistan from October 2019 and March 2020, and comprised male subjects aged 20-49 years who were employed at private schools, offices and banks, and commuted on a daily basis. Data was collected using the International Personality Item Pool, Brief Resilience Scale, Siddiqui Shah Depression Scale and the Clinical Anger Scale. Data was analysed using analysis of moment structure version 24. Results: Sample size for the current study is 187 (Male participants) were aged 19-29 years. Resilience had a significant negative mediating effect between depression (-0.14*) and neuroticism (-0.22*) personality traits, but was a non-significant mediator for other personality factors with respect to aggression and depression. Conclusion: Resilience was found to be beneficial in addressing aggression and depression among daily commuters. Key Words: Personality factors, Resilience, Depression, Aggression, Commuting time, Mediation.